The Definition of the Museum at the Intersection of Tradition and the Digital World - Csont, István (Ethnographica et Folkloristica Carpathica, 2025)
This study explores the evolving definition and role of museums in the digital age, focusing on the intersection of tradition and technological innovation. It illustrates the challenges of reaching a universally accepted concept by highlighting the historical development of the International Council of Museums’ (ICOM) definitions. The paper emphasizes that museums have always played a central role in preserving cultural heritage and facilitating education, but their tasks and methods have changed significantly over time. The 21st century has brought new expectations, including digital accessibility, audience engagement, and lifelong learning. The COVID-19 pandemic accelerated digital transformation, prompting museums to expand their online presence and educational offerings. The research discusses how virtual exhibitions, digital databases, and interactive technologies can enhance the relevance and outreach of museums. It also outlines the importance of international and national strategies in supporting digitisation efforts and cultural inclusion. Today, museums must adapt to societal needs while maintaining their core functions of preservation, education, and authenticity. The paper concludes that redefining museums requires balancing traditional knowledge mediation with modern, interactive approaches. Ultimately, museums are cultural hubs whose sustainability depends on their ability to innovate and connect with diverse audiences.